2020
DOI: 10.1016/j.pvr.2020.100205
|View full text |Cite
|
Sign up to set email alerts
|

Post-hoc analysis of injection-site reactions following vaccination with quadrivalent human papillomavirus vaccine in Japanese female clinical trial participants

Abstract: Aim The quadrivalent human papillomavirus (4vHPV) vaccine has demonstrated efficacy and immunogenicity and was generally well tolerated in clinical trials conducted in Japan. We report a detailed safety analysis of injection-site reactions in female Japanese 4vHPV clinical trial participants. Methods This post-hoc analysis included data from 2 double-blind, placebo-controlled phase II clinical trials of a 3-dose (Day 1, Month 2, Month 6) regimen of 4vHPV vaccine in Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Among the 23 included RCTs, all claimed to have used the exact randomized controlled procedures, but eight studies had an unclear risk of bias due to inadequate reporting of the random sequence generation 8,24,29,30,39,40,42,43 and eight studies showed inadequate reporting of allocation concealment. 7,8,26,30,34,40,42,43 In addition, two studies did not explain how participants and personnel were blinded, 30,34 and 11 did not explain how the outcome assessment was blinded. 25,[27][28][29][30][31]33,38,[40][41][42] The outcome data of one study were incomplete, 28 and there was an unclear risk of bias on the selectivity reports of 11 studies.…”
Section: Risk Of Bias Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 23 included RCTs, all claimed to have used the exact randomized controlled procedures, but eight studies had an unclear risk of bias due to inadequate reporting of the random sequence generation 8,24,29,30,39,40,42,43 and eight studies showed inadequate reporting of allocation concealment. 7,8,26,30,34,40,42,43 In addition, two studies did not explain how participants and personnel were blinded, 30,34 and 11 did not explain how the outcome assessment was blinded. 25,[27][28][29][30][31]33,38,[40][41][42] The outcome data of one study were incomplete, 28 and there was an unclear risk of bias on the selectivity reports of 11 studies.…”
Section: Risk Of Bias Resultsmentioning
confidence: 99%
“…The details of the study selection process are presented in Figure 1. After screening 1985 titles and abstracts and 198 full‐text articles, 23 trials that met our eligibility criteria were finally assessed 6–8,24–43 . All studies were two‐arm, RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suspension resulted in sharp declines in HPV vaccination (rate 14.3%) in Japan ( Nakagawa et al, 2020 ) [R]. While HPV has been shown effective and safe (minimal SAE and AE) ( Murata et al, 2020 ), Japan has not changed its official position ( Bodily et al, 2020 [r]; Ueda et al, 2020 [R]).…”
Section: Human Papillomavirus Vaccine [Sed-16 255–293; Seda-38 308–309; Seda-39 306–307; Seda-40 387–388; Seda-41 353–354]mentioning
confidence: 99%